Czy bibliści pamiętają jeszcze o szatanie? - Sokal, Bartłomiej Mateusz (The Biblical Annals, 2015)
The following paper aims to respond to some questions raised by L. Misiarczyk in his paper.2 Firstly, the author refers an opinion concerning shortage of studies about demonology and exorcisms in New Testament within Polish theological literature. The second part contains an analysis of the behavior of possessed people as described in New Testament accounts. Third part of the study endeavors to answer a question why the Gospel of John and Paul’s Letters do not mention demoniac possessions and exorcisms. Fourth chapter attempts to describe biblical anthropology that could help to understand whether biblical authors distinguished possessions from mental or physical maladies. Fifth and concluding part discusses suggestion of three possible ways of structuring the texts describing demons. While refuting some of the theses expressed by L. Misiarczyk, the paper underlines a number of valuable assets and topics presented by the author, that yet need to be discussed and reviewed.